Expression Profiling of microRNA From Peripheral Blood of Dairy Cows in Response to Staphylococcus aureus-Infected Mastitis - Luoreng, Zhuo-Ma; Yang, Jian; Wang, Xing-Ping; Wei, Da-Wei; Zan, Lin-Sen (Frontiers in Veterinary Science, 2021)
As the main pathogen causing dairy cow mastitis, Staphylococcus aureus can cause subclinical mastitis, which is difficult to be diagnosed. It seriously affects milk quality and the economic benefits of the dairy industry. Therefore, it is very necessary to find biomarkers for early diagnosis of S. aureus-infected mastitis in peripheral blood of dairy cows. In this study, S. aureus was used to infect the mammary gland tissues of dairy cows, and a mastitis model was successfully constructed. The RNAseq technology was used to determine the expression profiles of microRNA (miRNA) from peripheral blood of dairy cows infected with S. aureus at 0, 1, 3, 5, and 7 days. A total of 288 differentially expressed miRNAs (DIE-miRNAs) were found, of which 108 were known miRNAs and 180 were novel predicted miRNAs. Bioinformatics analysis results showed that the above DIE-miRNAs might be involved in 10 immune system-related signaling pathways (i.e., chemokine signaling pathway, leukocyte transendothelial migration, natural killer cell-mediated cytotoxicity, toll-like receptor signaling pathway, Jak-STAT signaling pathway, MAPK signaling pathway, Wnt signaling pathway, cell adhesion molecules, cytokine-cytokine receptor interaction and ECM-receptor interaction), thus regulating the process of S. aureus mastitis. It was also found that the expression variation of up-regulated expression of miR-320a, miR-19a, and miR-19b as well as down-regulated expression of miR-143, miR‑205, and miR‑24 reached a significant level on the 5th and 7th day of infection, suggesting that they might play an important biological role in mastitis and provide a direction for the research and development of molecular therapy technology for mastitis. However, at different times after S. aureus infection, miR-1301 was significantly up-regulated in peripheral blood. miR-2284r was significantly down-regulated, suggesting that these two miRNAs might be the new blood biomarkers for S. aureus-infected dairy cow mastitis. The above results laid a new foundation for the research and development of molecular diagnosis and biological therapy technology for S. aureus-infected mastitis in dairy cow.